Spatial variations of arsenic in groundwater from a transect in the Northwestern Hanoi - Nga, Dao Viet; Trang, Pham Thi Kim; Duyen, Vu Thi; Mai, Tran Thi; Lan, Vi Thi Mai; Viet, Pham Hung; Postma, Dieke; Jakobsen, Rasmus (Vietnam Journal of Earth Sciences, 2018)
Arsenic contamination of groundwater is a major health problem and has been a growing concern in the last decade in several regions of the world, especially in South and Southeast Asia, including the Red River delta, Vietnam. Regional groundwater studies have been carried out in the vicinity of Hanoi, on the banks of the Red River and its adjacent floodplains. In this study, the groundwater from a transect in the Northwestern area of Hanoi was examined. The results showed that 28.8% the wells of the B-B’ transect exceed the WHO guideline value for arsenic concentration in drinking water. The arsenic concentrations varied in a wide range from point to point, with the highest concentration found at Van Phuc and the lowest one found at Cam Yen. They also varied accordingly to the depth.References Anawar H.M., Akai J., Sakugawa H., Sakugawa H., 2004. Mobilization of arsenic from subsurface sediments by effect of bicarbonate ions in groundwater. Chemosphere, 54, 753-762. Appelo C.A.J., Postma D., 2004. Geochemistry, Groundwater and Pollution, second edition. Berg M., Tran H.C., Nguyen T.C., Pham H.V., Schertenleib R., Giger W., 2001. Arsenic contamination of groundwater and drinking water in Vietnam: A human health threat. Environmental Science & Technology, 35(13), 2621-2626. Berg M., Stengel C., Pham T.K.T., Pham H.V., Sampson M.L., Leng M., Samreth S., Fredericks D., 2007. Magnitude of arsenic pollution in the Mekong and Red River Delta - Cambodia and Vietnam. Science of the Total Environment, 372, 413-425. Chowdhury U.K., Biswas B.K., Chowdhury T.R., Samanta G., Mandal B.K., Basu G.C., Chanda C.R., Lodh D., Saha K.C., Mukherjee S.K., Roy S., Kabir S., Quamruzzaman Q., Chakraborti D., 2000. Groundwater Arsenic Contamination in Bangladesh and West Bengal, India. Environmental Health Perpectives, 108(5), 393-397. Eiche E., Neumann T., Berg M., Weinman B., Van Geen A., Norra S., Berner Z., Pham T.K.T., Pham H.V., Stuben D., 2008. Geochemical processes underlying a sharp contrast in groundwater arsenic concentrations in a village on the Red River delta, Vietnam. Applied Geochemistry, 23, 3143-3154. Fendorf S., Michael H.A., Van Geen A., 2010. Spatial and temporal variations of groundwater arsenic in South and Southeast Asia. Science, 328, 1123. Doi: 10.1126/Science.1172974. General Statics Office of Vietnam, 2015. Regional statistics of Area, Population and Population density. McArthur J.M., Ravenscroft P., Safuilla S., Thirlwall M.F., 2001. Arsenic in groundwater: Testing pollution mechanisms for sedimentary aquifers in Bangladesh. Water Resources Research, 31(1), 109-117. Postma D., Larsen F., Nguyen T.M.H., Mai T.D., Pham H.V., Pham Q.N., Jessen S., 2007. Arsenic in groundwater of the Red River floodplain, Vietnam: Controlling geochemical processes and reactive transport modeling. Geochimica et Cosmochimica Acta, 71, 5054-5071. Postma D., Larsen F., Nguyen T.T., Pham T.K.T., Jakobsen R., Pham Q.N., Tran V.L., Pham H.V., Murray A.S., 2012. Groundwater arsenic concentrations in Vietnam controlled by sediment age. Nature GeoScience. Doi: 10.1038/NGEO1540. Smedley P.L., Kinniburgh D.G., 2002. A review of the source, behavior and distribution of arsenic in natural waters. Applied Geochemistry, 17, 517-568. Smedley P.L., 2006. Sources and distribution of arsenic in groundwater and aquifers. In T. Appelo (Ed.), Arsenic in Groundwater - A World Problem, 4-33. Van Geen A., Bostick B.C., Pham T.K.T., Vi M.L., Nguyen N.M., Dao M.P., Pham H.V., Radloff K., Aziz A., Mey J.L., Stahl M.O., Harvey C.H., Oates P., Weinman B., Stengel C., Frei F., Kipfer R., Berg M., 2013. Retardation of arsenic transport through a Pleistocene aquifer. Nature, 501, 204-208. Van Geen, A., Zheng Y., Versteeg R., Stute M., Horneman A., Dhar R., Steckler M., Gelman A., Small C., Ahsan H., Graziano J.H., Hussain I., Ahmed K.M., 2003. Spatial variability of arsenic in 6000 tube wells in a 25 km2 area of Bangladesh. Water Resources Research, 39(5), 1140. Doi:10.1029/2002WR001617. World Health Organization, 2011. Guidelines for drinking-water quality, fourth edition. Winkel L.H.E., Pham T.K.T., Vi M.L., Stengel C., Amini M., Nguyen T.H., Pham H.V., Berg M., 2011. Arsenic pollution of groundwater in Vietnam exacerbated by deep aquifer exploitation for more than a century. PNAS, 108(4), 1246-1251.